2019
DOI: 10.1590/1982-0275201936e180075
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial needs of survivors of testicular cancer and evidence of validation of a brief scale

Abstract: The favorable prognosis of testicular cancer does not minimize immediate and late biopsychosocial implications. This study sought to determine these needs, and to evaluate the evidence of validation of a brief and specific scale for this population. A sample of 29 survivors of testicular cancer (n = 29) was assessed for distress (Distress Thermometer), anxiety and depression (Hospital Anxiety and Depression Scale), quality of life and cognitive impairment (Functional Assessment of Chronic Illness Therapy-Gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“… 29 One study found relationships of anxiety with cognitive-emotional regulation, sexual confidence and sexual functioning. 33 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 29 One study found relationships of anxiety with cognitive-emotional regulation, sexual confidence and sexual functioning. 33 …”
Section: Resultsmentioning
confidence: 99%
“… NA NR NR 5 Fair Manhães et al, 2019 33 HADS [≥8], 6.9% HADS [0–21], 3.2 (3.8) NA NR Sexual Confidence and Functioning (p = 0.04), Cognitive-Emotional Regulation (p = 0.001), and Specific Sexual Functioning (p = 0.04) were predictors of anxiety symptoms (R 2 = 61%). 8 Fair Whitford et al, 2019 29 NA HADS [0–21], Baseline Group A: 6.16 (4.08), baseline group B: 4.13 (3.69); FU Group A: 4.72 (3.36), FU Group B: 3.25 (3.69) NA Non sig: Treatment type (surgery alone vs surgery + chemo) NR Depression 1 Good Bandak et al, 2018 32 HADS [≥7], 7% NR NA NR NR 3 Good Skott et al, 2019 34 HADS [>7], 4.7% NR NA Non-sig: age NR 4 Fair Adams et al, 2018 30 NR CES-D10 [0–30]: baseline exercise group: 5.3 (4.7), baseline control: 4.5 (4.4) NA NR NR 5 Fair Manhães et al, 2019 33 HADS [≥9], 6.9% HADS [0–21], 1.8 (3.7) No NA Sexual Confidence and Functioning was associated with symptoms of depression (p = 0.01). Cognitive-Emotional Regulation (p = 0...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations